Acute on-snow severe injury events in elite alpine ski racing from 1997 to 2019: the Injury Surveillance System of the Austrian Ski Federation. Issue 11 (6th October 2020) - Barth, Michael; Platzer, Hans-Peter; Giger, Anton; Nachbauer, Werner; Schröcksnadel, Peter
Abstract : Objectives: The study aimed to (1) determine the incidence and gender-specific risk ratio of acute on-snow severe injury events (SIE) in elite alpine ski racing, (2) examine the development of SIE over 22 seasons, and (3) analyse SIE with respect to the severely injured body parts and structures. Methods: Data recorded in the Austrian Ski Federation's Injury Surveillance System over 22 seasons were analysed. The Austrian Ski Team consists of four groups: Team National (n=477), Team A (n=444), Team B (n=696) and Team C (n=608). Team National and Team A comprised World Cup, Team B European Cup and Team C junior alpine ski racers. Simple and multiple Poisson regressions were calculated. Results: The SIE incidence was 15.7 (95% CI 14.2 to 17.5) per 100 skier seasons. ACL injury events accounted for 70.8% of severe knee injury events and 48.6% of SIE. The incidence of severe ACL injury events was 7.6 (95% CI 6.6 to 8.9). Female World Cup alpine ski racers had a 1.65 times (95% CI 1.02 to 2.69) higher risk of severe ACL injury events than their male counterparts. Conclusion: The incidence of acute on-snow SIE in World Cup alpine ski racing was higher than previously reported. Despite various prevention efforts, the average seasonal incidence of SIE in World and European Cup alpine ski racers has grown from approximately 11 in 1997 to 23 in 2019; thus with roughly one more injured athlete every second season.